Impulse-Control Disorders in Parkinson’s Disease: A Meta-Analysis and Review of Case–Control Studies - Molde, Helge; Moussavi, Yasaman; Kopperud, Stine Therese; Erga, Aleksander Hagen; Hansen, Anita Lill; Pallesen, Ståle (Frontiers in Neurology, 2018)
Background: Although several case-control studies on the prevalence of Impulse Control Disorders (ICDs) in Parkinson’s Disease (PD) have been conducted, no meta-analytic study on this topic has previously been published. Thus, knowledge about the overall prevalence rate of ICD in PD and factors that might moderate this relationship is lacking. Method: Prevalence studies of ICDs in Parkinson’s disease were identified by computer searches in the MEDLINE, PsycINFO and Web of Science databases, covering the period from January 2000 to February 2017. Data for N = 4,539, consisting of 2,371 PD patients and 2,168 healthy controls, representing 14 case-control studies were included. Estimation of the odds ratio (OR) of ICDs in Parkinson’s disease compared to healthy controls was conducted using random-effects models. Mixed-effects models were applied in the moderator analysis of heterogeneity. Publication bias was estimated using a contour enhanced funnel plot, the Rüker’s test, and fail-safe N test for estimating the number of potential missing studies. Results: Overall, the results showed significantly higher ratios for several ICDs in Parkinson’s disease compared to healthy controls with the estimated overall ORs ranging between 2.07, 95% CI [1.26, 3.48] for having any ICDs, and 4.26, 95% CI [2.17, 8.36] for hypersexuality. However, the random-effects results for shopping were non-significant, though the fixed effects model was significant, OR = 1.66 (95%CI [1.21, 2.27]). The testing of potential moderator variables of heterogeneity identified the following two variables that were both associated with increased risk: Being medically treated for Parkinson’s disease and disease duration. The results must be interpreted with some caution due to possible small-studies effect or publication bias. Conclusion: Individuals with Parkinson’s disease seem to have a significantly greater risk of suffering from ICDs compared to healthy controls. Gambling, hypersexuality, eating, punding and hobbying are all ICDs significantly associated with PDs being medically treated for Parkinson’s disease.